Analysis of the relationship between a firm's ESG score and its valuation - Volzhan, Mariia (2025)
This bachelor thesis analyses the link between environmental, social, and governance (ESG) indicators and the market valuation of European firms. The aim is to test whether higher ESG scores correspond to higher valuation multiples (P/E, P/BV, P/S, EV/EBITDA, EV/EBIT). The study uses panel data from Bloomberg and Refinitiv for 2017–2022 and applies regression analysis with controls for firm size, industry, and time. Results show mostly weak or insignificant relationships, varying by pillar and provider. The work contributes by combining theory with empirical testing and critically assessing the financial relevance of ESG scores.